Progressive view on social justice: Netizen opinions about social justice warrior - Hartanto, Hartanto; Subandi, Subandi; Pavlova, Olga (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
Social justice warrior (SJW) is a pejorative term for individuals who fight for equality, environment, and gender. Because their progressive morals radically differ from the predominant values, the so-called social justice warriors spark controversies. This study aimed to describe netizens’ opinions about SJW and describe the dynamics of conflict or support in more detail. Text mining and opinion coding were used to elicit research data. The opinions that we gathered were analyzed in 2 stages: sentiment analysis and content analysis. The results of sentiment analysis are negative (445), neutral (86), and positive (90). Content analysis of the negative opinions showed the characteristics of sarcastic, rude, critical, and contemptuous (mocking/disrespecting). The style of positive sentiments (comments congruent with the phenomena) is divided into supportive, empathic, and motivational opinions. Negative opinions are more dominant because of netizens’ self-acceptance, the effects of informal social control in cyberspace, SJW’s presumed social non-compliance, and doubts of objectivity. Positive opinions can be explained by criticism of social contract theory, namely the demand to be more supportive of minority groups, sensitivity, and empathy (the ability to feel other groups' social conditions and environmental conditions).